Factors Associated With Acute and Chronic Wound Complications in Patients With Soft Tissue Sarcoma With Long-term Follow-up. (October 2018) - Karthik, Naveen; Ward, Matthew C.; Juloori, Aditya; Scott, Jacob; Mesko, Nathan; Shah, Chirag
Abstract : Objectives: To identify the rates of acute and chronic wound complications and factors associated in a cohort of patients treated for soft tissue sarcoma (STS) with modern radiotherapy (RT) and surgical techniques. Materials and Methods: An Institutional Review Board–approved database was used to identify all adult nonmetastatic patients treated for STS at a single institution between 2006 and 2015 with a minimum follow-up of 1 year. Factors associated with acute and chronic wound complications were analyzed using binomial logistic regression including interaction terms. Results: In all, 271 patients were identified with a median follow-up of 3.2 years. The rate of acute wound complications was 22.1%. On univariate analysis, trunk versus extremity location ( P <0.001), radiation therapy ( P =0.04), and preoperative therapy ( P =0.03) were associated with acute wound complications and a trend was noted for reconstruction ( P =0.07). On multivariate analysis, extremity tumors were associated with a higher rate of acute wound complications compared with trunk tumors without RT ( P =0.02). Utilization of RT was associated with increased risk for extremity tumors ( P =0.07). The rate of chronic wound complications was 3.3%. Radiation was associated with increased chronic wound complications ( P =0.03) and trends were noted for trunk versus extremity location ( P =0.08) and a history of acute wound complications ( P =0.12). Conclusions: Several factors associated with acute and chronic wound complications were identified in STS patients including timing of RT, tumor site, and reconstruction use. The development of acute wound complications may also be associated with an increased risk of chronic wound complications.